PERAN KOMUNIKASI INTERNAL KEPALA SEKOLAH DALAM MEMOTIVASI GURU SMA NEGERI 1 KALUKKU DI KABUPATEN MAMUJU - HAJJAD, MU'FIDATUL NURUL; WAHYUN, WAHYUN (LPPM Universitas Muhammadiyah Mamuju, 2023)
This research aims to focus on internal communication that occurs between leaders and subordinates, in this case the Principal and the Teachers and Teachers as subordinates who have the task of providing instruction to students who are always motivated to carry out their roles. This research is a qualitative research using informants as the main source of knowledge of the main problems observed at SMA Negeri 1 Kalukku in Mamuju Regency. Data analysis techniques use primary data by carrying out data reduction, data presentation and data conclusions. Data validity uses technical triangulation, method triangulation, and source triangulation. The Principal of SMA Negeri 1 Kalukku in Mamuju Regency is able to provide good and positive internal communication for teachers in teacher motivation, this has been proven to provide encouragement and motivation which has been given and carried out by the Principal of SMA Negeri 1 Kalukku in Mamuju Regency. The Principal's internal communication is carried out well, this can be seen from the Principal's ability to bring teachers closer together so that harmonization is built as an educator who has an interest in carrying out his role as an educator who carries out teaching and learning together with students, internal communication of the Principal of SMA Negeri 1 Kalukku in Mamuju Regency.